Risk assesment and management of exposure of health care workers to COVID-19 in a tertiary care hospital of South Gujarat - Bhatt, Krishnakant N.; Gamit, Amit; Patel, Ashish; Gohel, Kalpesh; Pujari, Shiv; Agrawal, Siddhant; Chauhan, Keshvi (International Journal Of Community Medicine And Public Health, 2021)
Background: The COVID-19 outbreak affected 215 countries worldwide and was declared global COVID-19 pandemic on 11th March 2020 by WHO. Healthcare workers (HCWs) in India are faced with an incredibly high number of patients per worker and because of high infectivity of COVID-19, having higher chances of getting COVID-19 infection. The objective of the study was the risk categorization of HCWs and provide recommendation for HCWs exposed to COVID-19 based on risk categorization. Methods: After obtaining informed and valid consent from HCWs based on standard WHO questionnaire HCW, who were exposed to COVID-19 were identified and categorised in to high risk and low risk health worker. Those who were at high risk of getting COVID-19 were advised quarantine for 14 days and rt pcr for Covid-19. Results: Out of 200 participants, 51% were male and 49% were female with the majority of them being in the age group of 18-28 (40%). Out of 200, 190 (95%) were exposed to COVID-19. Majority of HCWs who were having high risk of getting COVID-19 infection were young between age group of 18-28 (66,39.7%, p :0.091), male (91,59.6%, p<0.001), doctors (119, 80.9%, p<0.001). Conclusions: Young male doctors were more prone to get COVID-19 infection. It is important to protect HCWs from getting COVID-19 infections by taking various fundamental preventive measures like wearing proper PPE kits and adherence to strict hand hygiene.